2019
DOI: 10.3389/fonc.2019.00622
|View full text |Cite
|
Sign up to set email alerts
|

High Circulating Methylated DNA Is a Negative Predictive and Prognostic Marker in Metastatic Colorectal Cancer Patients Treated With Regorafenib

Abstract: Background: Regorafenib improves progression free survival (PFS) in a subset of metastatic colorectal cancer (mCRC) patients, although no biomarkers of efficacy are available. Circulating methylated DNA (cmDNA) assessed by a five-gene panel was previously associated with outcome in chemotherapy treated mCRC patients. We hypothesized that cmDNA could be used to identify cases most likely to benefit from regorafenib (i.e., patients with PFS longer than 4 months). Methods: Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 35 publications
2
33
1
Order By: Relevance
“…Liquid biopsies, a well-known noninvasive method, have aroused public attention as diagnostic materials for cancer, particularly circulating tumor DNA (ctDNA) in plasma. Taking advantage of technical advances, both genetic and epigenetic aberrations of cell-free DNA (cfDNA) can be detected [2] and have shown promising performance in clinical practice, including diagnosis [3][4][5][6][7][8], prognosis [9][10][11][12], and drug resistance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid biopsies, a well-known noninvasive method, have aroused public attention as diagnostic materials for cancer, particularly circulating tumor DNA (ctDNA) in plasma. Taking advantage of technical advances, both genetic and epigenetic aberrations of cell-free DNA (cfDNA) can be detected [2] and have shown promising performance in clinical practice, including diagnosis [3][4][5][6][7][8], prognosis [9][10][11][12], and drug resistance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In a Taiwanese CRC cohort, a quantitative polymerase chain reaction (qPCR) revealed that 86.1% of CRC patients exhibited hypermethylated BEND5 [15], suggesting that more sensitive biomarkers were worth investigating in Asian cohorts. In addition, assays of circulating methylated DNA (cmDNA) could be used as outcome predictors in chemotherapy and multikinase inhibitor-treated metastatic CRC patients [16]. These findings encouraged us to identify additional potential CRC-specific methylation markers, and combining multiple biomarkers in the early stage of CRC screening may provide more sensitive CRC early diagnoses [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Barault et al also suggested that plasmatic methylation changes of EYA4 me , GRIA4 me , ITGA4 me , MAP3K14-AS1 me and MSC me panel over time correlate with tumor response in metastatic CRC patients treated with chemoor targeted therapy [160]. Interestingly, using the same panel, Amatu et al reported that circulating methylated DNA normalized to the total amount of circulating DNA dynamics can reflect clinical response to treatment with regorafenib [161].…”
Section: Prognosis Prediction and Monitoringmentioning
confidence: 99%